Features of CFTR mRNA and implications for therapeutics development - Jackson, JaNise J.; Mao, Yiyang; White, Tyshawn R.; Foye, Catherine; Oliver, Kathryn E. (Frontiers in Genetics, 2023)
Cystic fibrosis (CF) is an autosomal recessive disease impacting ~100,000 people worldwide. This lethal disorder is caused by mutation of the CF transmembrane conductance regulator (CFTR) gene, which encodes an ATP-binding cassette-class C protein. More than 2,100 variants have been identified throughout the length of CFTR. These defects confer differing levels of severity in mRNA and/or protein synthesis, folding, gating, and turnover. Drug discovery efforts have resulted in recent development of modulator therapies that confer improvement in clinical outcomes for people living with CF. However, a significant portion of the CF population has demonstrated either no response and/or adverse reactions to small molecules. Additional therapeutic options are needed to restore underlying genetic defects for all patients, particularly individuals carrying rare or refractory CFTR variants. Concerted focus has been placed on rescuing variants that encode truncated CFTR protein, which also harbor abnormalities in mRNA synthesis and stability. The current mini-review provides an overview of CFTR mRNA features known to elicit functional consequences on final protein conformation and function, including considerations for RNA-directed therapies under investigation. Alternative exon usage in the 5’-untranslated region, polypyrimidine tracts, and other sequence elements that influence splicing are discussed. Additionally, we describe mechanisms of CFTR mRNA decay and post-transcriptional regulation mediated through interactions with the 3’-untranslated region (e.g. poly-uracil sequences, microRNAs). Contributions of synonymous single nucleotide polymorphisms to CFTR transcript utilization are also examined. Comprehensive understanding of CFTR RNA biology will be imperative for optimizing future therapeutic endeavors intended to address presently untreatable forms of CF.